Epidemiology and social inequalities of periodontal disease in Brazil - Pamella Valente Palma; Isabel Cristina Gonçalves Leite (Frontiers Media S.A., 2014)
Many studies discuss the relationship between social inequalities and their effect on health, but no consensus has been reached. This can be explained by the fact that this relationship is not found in all diseases, nor in all people, and is inconsistent over time. The intent of this study was to examine the epidemiology and the social inequalities of periodontal disease in Brazil through a comparison of the two most recent nationally-based epidemiological studies of oral health conducted in the country (SBBrasil). According to the SBBrasil 2003 and 2010 studies, there is perceptible improvement in the periodontal status of the population, however intra-regional differences persist, possibly explained by inequitable access to health services. These inequalities can adversely affect access to health information and network services, as well as interfere with the implementation of public policy. It was observed that the presence of dental calculus increases with age, reaching the highest prevalence among adults, close to 64%, and declining in the elderly. This group presented the worst periodontal condition, while adults had higher gingival bleeding.